EXPERIMENTATION OF PROBLEM POSING LEARNING MODEL ASSISTED OF AUTOGRAPH SOFTWARE TO STUDENTS’ MATHEMATICAL COMMUNICATION ABILITY IN TERMS OF STUDENT’S GENDER - Anim, Anim; Prasetyo, Yogo Dwi; Rahmadani, Elfira (Jurnal Ilmiah Peuradeun, 2019)
The study aimed at finding out in dept about the interaction between Problem Posing model assisted with Autograph Software with the student?s gender  to students' mathematical communication ability. This study used quantitative research with quasi experimental method. The approach used was a scientific one. The population of this study were all the Class X students of MAN Kisaran. The sample in this study were the students of class X-IPA1 and X-IPA-2 in MAN Kisaran of Asahan Regency. This study was conducted in the even semester of the academic year 2017/2018. Data analysis was done by 2-way ANOVA test. Based on the statistical calculation, it can be concluded that the value of Fcount<Ftable is 0.778 <3.12. This shows that Fcount<Ftable(0.778 <3.12) is not significant so that it can be concluded that H0 is accepted and Ha is rejected which means there is no interaction between learning with students? gender. The finding of students? actitivity aspects is based on direct observation. Female students are more active in learning but are weaker in reasoning, meanwhile Male ones are quick in reasoning but are less active in learning.